(untitled) (Research, Society and Development, 2022)
Objective: To identify the main pharmacological properties of Aloe vera. Methodology: This is an integrative review carried out in the electronic databases LILACS, SciELO and PubMed, using the following descriptors: “Aloe vera”, “Isolated Substances” and “Biological Activities”. Full articles, available in Portuguese and English, published between January 2011 and December 2021 were included. Results: The final sample consisted of 07 articles, published in the annual interval between 2011 and 2020. Regarding the approach of the articles found, check Most of them used the experimental study (n: 05), with a moderate level of evidence (III), followed by the randomized clinical trial (n: 02), with a strong level of evidence (II). The main pharmacological properties identified of Aloe vera were its anti-inflammatory action (reduction of erythema, exudate and pain), antimicrobial, antioxidant, healing (reduction of time for healing of acute and chronic wounds) and hypoglycemic (inhibition of post-hyperglycemic glucose elevation). -prandial). Conclusion: Numerous biological activities have been attributed to Aloe vera over the years, especially because of the combination of the various active compounds in its composition. It was found that this medicinal plant has several pharmacological effects, such as anti-inflammatory, antimicrobial, antioxidant, healing and hypoglycemic action.